2017
DOI: 10.1186/s12890-017-0478-3
|View full text |Cite
|
Sign up to set email alerts
|

The value of repeat radial-probe endobronchial ultrasound-guided transbronchial biopsy after initial non-diagnostic results in patients with peripheral pulmonary lesions

Abstract: BackgroundRadial-probe endobronchial ultrasound (rEBUS)-guided transbronchial biopsy (TBB) is invaluable in the diagnosis of peripheral pulmonary lesions (PPLs); however, in certain instances, the procedure has to be repeated because of initial non-diagnostic procedure(s). Little if any literature has been published on this issue. Therefore, the aim of this study was to investigate the utility of repeat rEBUS-guided TBB in achieving a definitive diagnosis of PPLs.MethodsAll patients who underwent rEBUS-guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…The authors concluded that RP‐EBUS is comparable with fluoroscopy for diagnosis of peripheral lung lesions with no associated risk of radiation 11 . From that point, other studies have described RP‐EBUS‐guided TBB as a feasible and effective technique for diagnosis of peripheral lung lesions 12‐14 . In our study with RP‐EBUS‐guided forceps TBB the sensitivity and accuracy were 67.5% and 69.8%, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…The authors concluded that RP‐EBUS is comparable with fluoroscopy for diagnosis of peripheral lung lesions with no associated risk of radiation 11 . From that point, other studies have described RP‐EBUS‐guided TBB as a feasible and effective technique for diagnosis of peripheral lung lesions 12‐14 . In our study with RP‐EBUS‐guided forceps TBB the sensitivity and accuracy were 67.5% and 69.8%, respectively.…”
Section: Discussionsupporting
confidence: 57%
“…mNGS is an unbiased and rapid technique capable of detecting a broad range of pathogenic bacterial, viral, fungal, and parasite simultaneously in clinical samples. R-EBUS is a safe and valuable technique, which has been demonstrated to increase diagnostic yield for PPLs [29]. Current clinical use of R-EBUS is mainly in the localization of peripheral pulmonary lesions prior to biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…The bronchoscopic exam was primarily conducted by pulmonary fellows, as previously described, under the supervision of eight rotating pulmonary faculty in attendance [13, 14]. In brief, conventional bronchoscopy (BF-1 T260; Olympus Medical Systems Corp., Tokyo, Japan) was first performed to inspect the tracheobronchial tree after the patient received local anesthesia with lidocaine in the upper airway and intramuscular fentanyl for analgesia.…”
Section: Methodsmentioning
confidence: 99%